Ibrutinib inhibits BMX-dependent endothelial VCAM-1 expression in vitro and pro-atherosclerotic endothelial activation and platelet adhesion in vivo - Kohs, Tia C. L. (2022)
© 2022 The Author(s) under exclusive licence to Biomedical Engineering Society.